2017
DOI: 10.18677/encibio_2017a34
|View full text |Cite
|
Sign up to set email alerts
|

Cultivares De Mandioca Submetidas a Adubacao Fosfatada Na Amazonia Sul Ocidental

Abstract: RESUMOA mandioca está entre as cinco principais fontes de carboidratos de toda população mundial, é cultivada para diversas finalidades e pode ser utilizada para alimentação humana ou animal em diferentes formas. O cultivo de mandioca é uma atividade desenvolvida caracteristicamente por pequenos produtores, que necessitam de alta produtividade em uma pequena área. Oriunda da região amazônica, seu cultivo é abundante em Rondônia, porém ainda devem ser empregadas praticas edáficas para o seu melhor rendimento. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
(1 reference statement)
2
2
0
Order By: Relevance
“…The results obtained in each crop show what other studies have already found: Cuvaca et al ( 2017) observed an increase in root productivity with the addition of phosphate fertilizer; Silva et al (2014), Tironi et al (2015), Omondia et al (2019) and Kang et al (2020) observed variation in productivity between cassava cultivars and variation for cultivars in different crops due to meteorological differences and the chemical attributes of the soil in the study sites; and Enck et al (2017) found no difference in productivity between cassava cultivars fertilized with increasing doses of P.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…The results obtained in each crop show what other studies have already found: Cuvaca et al ( 2017) observed an increase in root productivity with the addition of phosphate fertilizer; Silva et al (2014), Tironi et al (2015), Omondia et al (2019) and Kang et al (2020) observed variation in productivity between cassava cultivars and variation for cultivars in different crops due to meteorological differences and the chemical attributes of the soil in the study sites; and Enck et al (2017) found no difference in productivity between cassava cultivars fertilized with increasing doses of P.…”
supporting
confidence: 86%
“…For the commercial root number, there is a tendency for variations to occur due to genetic factors inherent to each cultivar. There would not be an effect of the application of increasing P doses, a fact also observed by Enck et al (2017), who found no difference in the number of roots between cassava cultivars fertilized with increasing doses of P. Similar results for the commercial root number have also been reported by Tironi et al (2015), who observed a difference in the commercial root number of five cassava cultivars, as well as a difference between the two agricultural crops evaluated.…”
supporting
confidence: 82%
See 2 more Smart Citations